The Tip of the Iceberg: Situating the U.S. Arctic Discourse as an Arctic Ally or Adversary - Alexandria Jessika Fenn 1998- (2023)
This thesis investigates the United States' interests in the Arctic region as it has transitioned into a large Arctic region player over the past few decades. As climate change opens up the Arctic region, more international players have entered the region. However, the increased international spotlight has led to heightened tensions in the region. Geopolitical tensions and expanding economic opportunities are driving states to issue strategies concerning their position and interests in the Arctic region. Many scholars and researchers have criticized the U.S. for its sudden involvement in the region, prompting questions regarding its sincerity and underlying interests in the region. This study conducts a two-part discourse analysis to compare the formally stated interests of the U.S. Arctic Policies with the underlying discourse and interests expressed by U.S. political actors in their statements about the Arctic, Alaska, and Greenland. The analysis covers the period from 2009 to the beginning of 2023. The discourse findings are analyzed under the theoretical framework of neocolonialism, capitalism, and human securitization theory. The main finding is that the U.S. Arctic Policies’ strategies and interests differ from the discourse of U.S. political actors, with economic opportunities and military security being the main interests of the U.S. in the Arctic region. U.S. Arctic interests are more concerned with domestic priorities than foreign ones. As U.S. Arctic interests are driven by neocolonialism motives and capitalistic behaviors, the human security of non-state actors in the Arctic is hindered, such as the Arctic Indigenous peoples. The U.S. focuses more on the human security of Alaskan natives than other Arctic States’ Indigenous peoples. The U.S. Arctic Policies are published to ameliorate its reputation, as all the U.S. Arctic interests are based on U.S. securitization, not cooperation. Concluding that the U.S.’s Arctic Policy priorities do not align with the interests found within the U.S. political ...